From Africa to America: religion and adaptation among Ghanaian immigrants in New York - Biney, Moses O. (Religion, race, and ethnicity series, 2011)
Coming to America : Ghanaians and United States immigration -- By the Hudson River : Ghanaian presence in New York -- Remembering the homeland : Ghana and its people -- How shall we sing the Lord's song? : an overseas mission -- Compound house : communal life and welfare -- Conflict and cohesion : gender and intergenerational relations -- Ebenezer : spirituality and identity -- Pedaling on both sides : analysis and conclusion